2022
DOI: 10.1136/bmjopen-2022-060785
|View full text |Cite
|
Sign up to set email alerts
|

Scoping review of costs of implementation strategies in community, public health and healthcare settings

Abstract: ObjectivesTo identify existing evidence concerning the cost of dissemination and implementation (D&I) strategies in community, public health and health service research, mapped with the ‘Expert Recommendations for Implementing Change’ (ERIC) taxonomy.DesignScoping review.Data sourcesMEDLINE, EMBASE, CINAHL, PsycINFO, Scopus and the Cochrane Library were searched to identify any English language reports that had been published between January 2008 and December 2019 concerning the cost of D&I strategies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 92 publications
0
6
0
Order By: Relevance
“…Moreover, there remains significant variability in how researchers operationalize, apply, and report strategies (individually or in combination) and outcomes [ 21 , 22 ]. Still, synthesizing data related to using individual strategies would help researchers replicate findings and better understand possible mediating factors including the cost, timing, and delivery by specific types of health providers or key partners [ 23 25 ]. Such an evidence base would also aid practitioners with implementation planning such as when and how to deploy a strategy for optimal impact.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there remains significant variability in how researchers operationalize, apply, and report strategies (individually or in combination) and outcomes [ 21 , 22 ]. Still, synthesizing data related to using individual strategies would help researchers replicate findings and better understand possible mediating factors including the cost, timing, and delivery by specific types of health providers or key partners [ 23 25 ]. Such an evidence base would also aid practitioners with implementation planning such as when and how to deploy a strategy for optimal impact.…”
Section: Introductionmentioning
confidence: 99%
“…A recent scoping review of implementation strategy costs found that multicomponent interventions ranged from $7288 to $3 million. 13 This wide range of costs can be partly attributed to the varying scales, contexts, and settings of the interventions, as well as the complexity of the intervention strategies. Costs ranged from $7570 to $65,335 per clinic for multicomponent interventions focused on primary care clinics.…”
Section: Discussionmentioning
confidence: 99%
“…Not only do cost analyses provide the cost of employing implementation strategies in a specific setting but they also inform the replication costs of these implementation strategies in other settings 12 . Currently, there is a dearth of literature on implementation strategy costs, particularly from the health care system perspective; a recent scoping review found that among the 52 studies included, only 8 described implementation strategy costs from the perspective of the health care system 13 . It is essential to estimate the costs of these strategies for health care systems to bridge the research-practice gap in using implementation strategies.…”
mentioning
confidence: 99%
“…Some examples of these implementations strategies include; i) conduct educational meetings, defined as “hold meetings targeted toward different stakeholder groups to teach them about the clinical innovation,” ii) build a coalition, defined as “recruit and cultivate relationships with partners in the implementation effort,” iii) access new funding defined as “access new or existing money to facilitate the implementation” [ 33 ]. The ERIC project classification has been used in scoping reviews in other health fields such as dementia [ 34 , 35 ] and costing of implementation strategies [ 36 ] scoping reviews in preference to other taxonomies as it is more detailed with a conceptually clear description of strategies.…”
Section: Methodsmentioning
confidence: 99%